2014
DOI: 10.5194/bg-11-3163-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of commonly used gas analysers for methane eddy covariance flux measurements: the InGOS inter-comparison field experiment

Abstract: Abstract. The performance of eight fast-response methane (CH 4 ) gas analysers suitable for eddy covariance flux measurements were tested at a grassland site near the Cabauw tall tower (Netherlands) during June 2012. The instruments were positioned close to each other in order to minimise the effect of varying turbulent conditions. The moderate CH 4 fluxes observed at the location, of the order of 25 nmol m −2 s −1 , provided a suitable signal for testing the instruments' performance.Generally, all analysers t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 42 publications
4
59
0
Order By: Relevance
“…more variable C CH 4 ), the flux uncertainty increases substantially and becomes much greater than F CH 4 , while the relative importance of σ 2 C n decreases. Thus, we expect the 10-fold greater CH 4 flux detection limit estimated by Peltola et al (2014) to be due to the higher variability in C CH 4 over land than at our marine site (for onshore winds only). Over the open ocean where σ C a in CH 4 is likely to be even lower than at PPAO, the flux detection limit for CH 4 should slightly decrease.…”
Section: Detection Limit Of Ch 4 Flux Measurementmentioning
confidence: 80%
“…more variable C CH 4 ), the flux uncertainty increases substantially and becomes much greater than F CH 4 , while the relative importance of σ 2 C n decreases. Thus, we expect the 10-fold greater CH 4 flux detection limit estimated by Peltola et al (2014) to be due to the higher variability in C CH 4 over land than at our marine site (for onshore winds only). Over the open ocean where σ C a in CH 4 is likely to be even lower than at PPAO, the flux detection limit for CH 4 should slightly decrease.…”
Section: Detection Limit Of Ch 4 Flux Measurementmentioning
confidence: 80%
“…Grund et al, 2001), and it was also extended to correct eddy-covariance flux measurements of trace gases (e.g. Mauder et al, 2013;Peltola et al, 2014). This technique has been used to study higher-order statistics in the convective boundary layer (e.g.…”
Section: Llnl Windcube V2mentioning
confidence: 99%
“…Nowadays, new and better instrumentation is available for measuring turbulent fluxes of energy and matter using the EC technique. Recent studies have compared commercially available gas analysers, focusing on precision, stability and systematic and random errors both for CO 2 fluxes (Burba et al, 2008;Ibrom et al, 2007a;Järvi et al, 2009) and methane (CH 4 ) and nitrous oxide (N 2 O) fluxes (Detto et al, 2011;Peltola et al, 2013Peltola et al, , 2014Rannik et al, 2015). However, only a few studies have reported an inter-comparison between EC software packages, and all focusing only on energy and CO 2 fluxes (Fratini and Mauder, 2014;Mauder et al, 2007Mauder et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%